Vaccination practices and knowledge among adults with hemoglobinopathies in Greece: a nationwide survey - Sophia Delicou; Konstantinos Manganas; Aikaterini Xydaki; Loukia Evliati; Ioanna Myrilla; Leonidas Rubatis; Stavroula Kostaridou (SAGE Publishing, 2024)
Background: Hemoglobinopathies, such as sickle cell disease and thalassemia, are genetic disorders that affect hemoglobin structure or production, leading to various health complications, including an increased risk of infections. Vaccinations play a crucial role in managing these conditions by providing essential protection against preventable diseases. Ensuring timely and appropriate immunizations is vital for reducing infection-related morbidity and improving the overall health and quality of life for affected individuals. Objectives: Our objective was to assess vaccination coverage, as well as knowledge, attitudes, and practices toward vaccination in Greek patients with hemoglobinopathies. Design and methods: A nationwide survey of hemoglobinopathy patients in Greece using a 37-item questionnaire was conducted anonymously via Google Forms. It covered demographics, previous vaccinations, vaccine-preventable infections, beliefs about vaccines, and antibiotic prophylaxis post-splenectomy. The survey was distributed through Thalassemia and Sickle Cell Units and organizations. Results: Participants were predominantly university-educated married women aged 30-50 years with transfusion-depended thalassemia ( n  = 149, 60.5%) or sickle cell anemia ( n  = 52, 21.1%). Reported childhood vaccination rates aligned with Greece's national immunization program. However, adult coverage was suboptimal across all age groups for measles (10%), varicella (27%), zoster (2% for over 50 years old individuals), hepatitis A (13.9% of those with chronic liver disease) and hepatitis B (41%), pneumococcal (81.3%), meningococcal (37%), tetanus (20.3%), and influenza (67.1%) vaccines compared to guidelines. Participants relied predominantly on healthcare providers for vaccine information but perceived limited engagement. Those over age 50 demonstrated lower adult vaccination rates and higher misconceptions compared to younger cohorts. Conclusion: Addressing educational and access gaps could help protect this vulnerable population. Our findings highlight the need for coordinated efforts to optimize adult immunization for those with hemoglobinopathies.